2018
DOI: 10.1186/s40068-018-0124-y
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of community based watershed management practices: emphasis on technical fitness of physical structures and its effect on soil properties in Lemo district, Southern Ethiopia

Abstract: Background: Soil erosion is one of the major causes for food insecurity, and environmental degradation in Ethiopia. To reduce erosion effects, soil and water conservation practices have been promoted at farm level and watershed scale-executed via mass-community mobilization program. In Lemo district, little information is available on suitability of soil conservation practices implemented through this program. The aim of this study was to assess technical fitness of physical soil conservation structures implem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 15 publications
4
12
0
Order By: Relevance
“…The recommended and scientific standards have not been given due attention. This result was confirmed by Bekele et al (2018) who stated that the spaces between successive graded bunds were somewhat wider than the recommended standards mainly due to lack of technical assistance in bund design and layout. Such conditions more likely increase erosion risk on the cropland due to the large amount of runoff accumulation in bund ditches (Molla and Sisheber 2017).…”
Section: Some Limitations Of the Swc Practices Affecting Its Effectivmentioning
confidence: 55%
“…The recommended and scientific standards have not been given due attention. This result was confirmed by Bekele et al (2018) who stated that the spaces between successive graded bunds were somewhat wider than the recommended standards mainly due to lack of technical assistance in bund design and layout. Such conditions more likely increase erosion risk on the cropland due to the large amount of runoff accumulation in bund ditches (Molla and Sisheber 2017).…”
Section: Some Limitations Of the Swc Practices Affecting Its Effectivmentioning
confidence: 55%
“…Plot size was also found to have a positive effect on farmers' perception to invest in SWC technologies in northwestern highlands of Ethiopia (Belachew, Mekuria and Nachimuthu 2020; Moges and Taye 2017; Teshome, de Graaff and Kassie 2016), in eastern Ethiopia (Sileshi et al 2019), and in Lemo district, southern Ethiopia (Bekele, Aticho and Kissi 2018). It was also found to exert a positive and signi cant effect on the adoption of soil management practices in southwestern Uganda (Mugonola et al 2013) and in West African Sahel (Kpadonou et al 2017).…”
Section: Factors Affecting Use Of Improved Structural Swc Measuresmentioning
confidence: 94%
“…In recent studies, access to extension service was found to have a significant effect on the adoption of SWC practices in different parts of the country: northwest Ethiopian highlands (Belachew et al 2020;Moges and Taye 2017); Wereillu district, northern Ethiopia (Asfaw and Neka 2017); Gibe basin, southwest Ethiopia (Mengistu and Assefa 2019); Lemo district, southern Ethiopia (Bekele et al 2018); and, Gusha Temela watershed, Arsi, Ethiopia (Biratu and Asmamaw 2016). Likewise, contact with extension service providers was found to have positive effect on the adoption of SWC measures in Techiman Municipality of Ghana (Darkwah et al 2019), in Tanzania (Lasway et al 2020;Shrestha and Ligonja 2015), and in the Rwizi catchment of south western Uganda (Mugonola et al 2013).…”
Section: Extension Contactmentioning
confidence: 99%